Atypical bilateral cerebellopontine angle medulloblastoma: differential diagnosis, immunohistochemical features and radiological presentation - Kelvin M. Pińa Batista; Sayoa Alvarez de Eulate-Beramendi; María Rico; Victor Rodrigo; Yordy E. Batista Batista; Kenia Y. Alvarez Reyes (Contemporary Oncology, 2017)
Medulloblastoma (MB) is a highly aggressive soft tissue neoplasm, classified as a primitive neuroectodermal tumor. It is the most common posterior fossa tumor in children, but occurs rarely in adults. MB accounts for approximately 20% of all primary central nervous system (CNS) tumors of childhood, while its incidence is around 1% of adult brain tumors. Most often it occurs in the cerebellum. We report a case of multicentric MB involving the bilateral cerebellopontine angle (CPA) and right cerebellar hemisphere. The tumor showed isointensity on T1/T2-weighted images, and slight hyperintensity on T2-weighted fluid-attenuated inversion-recovery (FLAIR) images. The MB had restricted diffusion on diffusion-weighted images (DWI). It was not easy to make an accurate diagnosis before biopsy. The lesion in our patient presented with atypical MR image features of medulloblastoma. To our knowledge, this is the first case of bilateral CPA MB.